Subtle behavioral alterations in the spontaneous behaviors of MPTP mouse model of Parkinson’s disease - Hao Zhong; Kangrong Lu; Liping Wang; Wanshan Wang; Pengfei Wei; Xuemei Liu (Translational Psychiatry)
Abstract Midbrain dopamine (DA) neurons are essential for regulating movement, emotion, and reward, with their dysfunction closely linked to Parkinson’s disease (PD). While DA neurons in the substantia nigra pars compacta (SNc) and ventral tegmental area (VTA) have known overlapping roles in behaviors such as depression and reward, their distinct contributions to subtle spontaneous behaviors remain insufficiently understood. In this study, we utilized a 3D behavioral analysis platform powered by machine learning to explore motor and nuanced behavioral changes in a subacute MPTP mouse model of PD. This investigative approach was combined with cell-type-specific genetic ablation of DA neurons in both the SNc and VTA. Our findings highlight significant deficits in rearing, walking, and hunching behaviors correlated with the loss of SNc DA neurons, but not VTA DA neurons, alongside increased overall movement, reduced movement precision, and pronounced right-sided lateralization. These subtle features, particularly rearing deficits and lateralization, emerge as critical behavioral biomarkers of SNc DA neuron loss, thereby enhancing the translational relevance of PD models.